Implementasi Pembelajaran Fonologi Dengan Model Project-Based Learning Berbantuan Flipbook - Sri Mujiatun; Ngatmini Ngatmini (Politeknik Kampar, 2023)
Language is a very complex phenomenon. Indonesian is a communication tool that is one of the characteristics of the Indonesian nation and is used as the national language. Indonesian language lessons are one of the subjects that must be taught in elementary schools. Phonology is a field of linguistics that studies, analyzes, and discusses sequences of language sounds. The aim of this research is to describe phonology with the flipbook-assisted PjBL model. Data were collected from several journals that were reviewed and then analyzed. The results of the study show that the PjBL model with flipbook media is able to help elementary school students implement Indonesian phonology.